2013
DOI: 10.1007/s13142-013-0226-z
|View full text |Cite
|
Sign up to set email alerts
|

School factors as barriers to and facilitators of a preventive intervention for pediatric type 2 diabetes

Abstract: School-based interventions are essential to prevent pediatric obesity and type 2 diabetes. School environmental factors influence implementation of these interventions. This article examines how school factors acted as barriers to and facilitators of the HEALTHY intervention. The HEALTHY study was a cluster-randomized trial of a multicomponent intervention implemented in 21 schools. Interview data were analyzed to identify barriers and facilitators. Barriers included teacher frustration that intervention activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…strict control of information by HC) the organizational adoption of the EWC (9) re-emerged during implementation, reinforcing the strong connection between adoption and implementation and their potential impacts on reach and effectiveness (6) . Other qualitative studies have highlighted the importance of taking into consideration the contextual nature of factors associated with healthy eating programme and policy implementation (21)(22)(23) . Granular-level analysis of sub-themes revealed salient differences between partner groups that are contextual in nature and are particularly important given the setting of an intervention implemented by cross-sector partners.…”
Section: Discussionmentioning
confidence: 99%
“…strict control of information by HC) the organizational adoption of the EWC (9) re-emerged during implementation, reinforcing the strong connection between adoption and implementation and their potential impacts on reach and effectiveness (6) . Other qualitative studies have highlighted the importance of taking into consideration the contextual nature of factors associated with healthy eating programme and policy implementation (21)(22)(23) . Granular-level analysis of sub-themes revealed salient differences between partner groups that are contextual in nature and are particularly important given the setting of an intervention implemented by cross-sector partners.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these challenges may not be unique to the South African setting. Schools have been described as highly complex systems, which makes the successful delivery of complex, multicomponent health interventions a daunting task [ 30 ]. In an effort to create a sustainable programme that would not be seen as an additional burden, the HK research team, to a certain degree, expected school staff to serve as multicomponent programme planners and implementers.…”
Section: Discussionmentioning
confidence: 99%
“…A key barrier identified within the inner context was school district bureaucracy. Previous studies have also identified how bureaucratic factors, such as lack of supported staff time to support implementation and/or lack of funding and prioritizing by school administration, are barriers to implementing new school-based policies and health promotion programs [34,35]. As demonstrated in the case studies, the role of the program coordinator provided crucial oversight and structure for the program, and without funding for this full-time dedicated coordinator position, the referral systems may not have been successfully implemented.…”
Section: Discussionmentioning
confidence: 99%